Analysis of laterally loaded group of piles located on sloping ground. Issue 5 (3rd July 2020) - Deendayal, R.; Muthukkumaran, K.; Sitharam, T. G.
Abstract: In this paper, a finite element numerical analysis was carried out to study the behaviour of group of piles located on sloping ground using finite element analysis software PLAXIS 3D. A pile of 0.305 m diameter and 9.1 m length was arranged in 3 × 3 group pattern with spacing equal to three times the pile diameter (3D) and was modelled by PLAXIS 3D. The group of piles was embedded into a soil profile consisting of soft to medium-stiff clay and silts underlain by sand. A parametric study was carried out to study the behaviour of group of piles located on sloping ground surface (1V:5H and 1V:3H slopes) and subjected to lateral loads. The effect of slopes on pile capacity, the behaviour of lateral deflections and bending moment profile of front, middle and back rows of group of piles were studied.